A Decision Tree Based Recommender System for Backpackers Accommodations - Mat Amin, Maizan; Yep Ai Lan, Jannifer; Makhtar, Mokhairi; Rasid Mamat, Abd (International Journal of Engineering and Technology, 2018)
Backpackers often travel for a longer period of time, have their own budgets and requirements on accommodations. The existing systems do not offer personalized recommendation criteria and some proposed inefficient recommender system (RS) for users. Moreover, other than information searching from websites and bloggers, only limited systems were specifically designed for backpackers’ accommodations recommender system. An observation and online survey was conducted to get the information from backpackers regarding their preferences while looking for the accommodations. Fifty (50) respondents were involved in the survey and the data have been analyzed and were classified to build a decision tree. The decision tree model then implemented in the Backpackers’ accommodations Recommender System (BRS). BRS offers a convenient way and solution for backpackers by including decision tree technique in the system to suggest best accommodations suit to backpacker’s preferences.